PI for assessing effectiveness of energy management processes in water systems - Duarte, P. (2009)
The current paper aims at the establishment of criteria and performance measures for the assessment of the effectiveness of energy management processes in water supply systems. The main objectives that generally motivate the implementation of energy management strategies are identified, assessment criteria for each objective and the corresponding performance indicators to be used are recommended. Three new performance indices for evaluating energy efficiency of systems are proposed and tested, and information provided and advantages and shortcomings of each indicator are discussed.